The storage and preservation of Philippine films in the ABS-CBN Film Archives and the MOWELFUND Audiovisual Archive - Cruzado, Joseph Angelo E.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
Preservation and storage practices vary depending on the nature of the records that the archives collect. As for audiovisual materials, its physical and chemical components are more perishable than that of a paper. Film preservation and storage is the focus of the study and is applied in Philippine context. This study aims to know the best preservation and storage practices suitable for the Philippine setting through the two subject institutions: the ABS-CBN Film Archives and the MOWELFUND Audiovisual Archive.
The respondents were Ms. Mary Del Pilar and Mr. Eligio Macatangay, Jr. of the ABS-CBN Film Archives and Mr. Manrique Orellana of the MOWELFUND Audiovisual Archive. Their collections, guidelines and standards for storage and preservation, budget allocation, background/profile of archivist/librarian, and administration support were explored to meet the objectives of the study.
It was found out that the two institutions were adapting to the standard set by SOFIA and IFLA. They differ on the kind of their collection thus, they also differ on the practices they apply on their institutions. However, their main difference is the budget that they allocate in their preservation and storage practices. But this does not stop both of the institutions in providing the best preservation and storage practice for their collection. Recommended preservation and storage guidelines were made after the study for an effective film/audiovisual archives.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Audio-visual archives -- Philippines -- Quezon City; Film archives -- Philippines -- Quezon City; Motion pictures -- Storage -- Philippines -- Quezon City; Motion pictures -- Preservation and restoration -- Philippines -- Quezon City